Analysis of Factors Affecting the Performance of Employees in Frozen Product Companies in Jakarta - Yosandi Yulius; Yopi Yulius; Abdullah Muksin (Journal of Accounting and Finance Management, 2023)
To find out the increase in employee performance, in addition to evaluating work results, the quality and quantity of work is also seen several factors that influence employees to improve their performance. These factors include work motivation, work communication and work stress. This descriptive research uses a quantitative approach with an associative research type, which measures the relationship and influence between variables of work motivation, communication and work stress on employee performance, with 97 respondents at several frozen companies in Jakarta. Data analysis, multiple correlation tests, multiple regression tests and hypothesis testing using statistical tests with the SPSS 27.0 application for windows. The results of the multiple correlation test between work motivation, work communication and work stress with employee performance are 0.885, meaning that they have a very strong and positive relationship. Meanwhile, the results of the multiple regression test obtained a regression equation Y = 7.724 + 0.330X1 + 0.311X2 + 0.196X with a determination coefficient value of 0.772, meaning that the variables of work motivation, work communication and work stress contribute to influencing employee performance by 77.2%. The results of the t test and F test show that all hypotheses are accepted, which means that all independent variables, either partially or simultaneously have a positive and significant effect on employee performance.